PENGARUH SUASANA TOKO, KUALITAS PELAYANAN, DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN PADA BERUNDING COFFEE YOGYAKARTA - Handoko, Jonathan Lukas (Universitas Ciputra Surabaya, 2023)
Some recent years, Indonesians have experienced quite significant increase of coffee consumption. World Coffee Organization states that the increase of coffee consumption occurs as 44% in recent ten years, while Global Agricultural Information Network predicts that national coffee consumption keeps on increasing with the range of 13,9% per year. That opportunity is used by Berunding Coffee’s owner as the reason to open the first coffee shop in August 2020. Based on its name, Berunding Coffee places service value as main thing that has to be own by coffee shops and that thing can be started with